Serum Levels of Vimentin and Oxyntomodulin in Women with Breast Cancer. Comparative Study - faiq, Maryam A; Ahmed, Salam S; Mohammed, Thaer J (International Journal of Psychosocial Rehabilitation, 2020)
Background: Breast cancer is the most frequent malignancy among women worldwide, accounting for 25 % of all cancers.(1) The incidence rates of breast cancer have been increasing almost in all countries to reach more than two million cases in 2018.(2) Vimentin (VIM), is a 57 KDa protein is one of the most widely expressed and highly conserved proteins of the type III intermediated filament protein family.(3) VIM plays a significant role in holding the organelles in the cytosol it has a flexible nature, allowing it to respond to mechanical stress and by interacting with other structural proteins, like microtubules, it makes the cell rigid and sturdy.(4) Oxyntomodulin (OXM) is a 44.499 KDa peptide hormone produced by the neuroendocrine cells of the ileum.(5) Oxyntomodulin characterized by, ability to interact with and modulate the gastric oxyntic gland.(6) Materials & Methods: This is a cross sectional hospital based study. This study was carried out at the Oncology Center in Kirkuk City-Iraq from the1st of November 2019 to the end of May 2020. Forty-five women with breast cancer were considered as a study group. Forty-tow apparently healthy women without breast cancer and with a negative family history for the first and second degree relatives of breast cancer were consider as a control group. By using a sterile disposable syringe 5 mls of venous blood sample was drawn from each woman and was kept in a plain tube and allowed to clot at room temperature, then each sample was centrifuged at 3000 rpm to obtain serum. Serum of the patients and controls had assay for Vimentin and Oxyntomodulin by ELISA. Results: The mean serum level of vimentin was significantly higher in women with breast cancer compared to control at a P value of 0.006, while the mean serum level of oxyntomodulin was lower in women with breast cancer as compared with the control group, this result was highly significant at a P value of 0.003. This study found that there was a negative correlation between S.OXM and S. VIM level in breast cancer women (r = -0.135). Conclusion: This study reveals that there was a negative correlation between S.OXM and S. VIM level in breast cancer women r = -0.135.